LIFE IN A CONTAMINATED WORLD: THE PESTICIDES AND THE BIRDS POPULATION DECLINE - BISWAS, SHATABDI; SINGH, PUJA; DAS, BHABANA; DAS, JYOTISMITA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Background: The extensive use of pesticides has been increasing with the modernization of agricultural system, vector borne disease control, pest control, etc. Pesticides not only affect the environment, but also affect the wildlife including birds. Generally the chemical pesticides which are tremendously used in the agricultural fields fall under three major groups, which are organochlorine, organophosphate and carbamate [1]. Aim: To review the effect of pesticides in population decline of birds. Materials and Methods: The related data on pesticide’s contribution to the bird’s decline were obtained from digital data bases like Google Scholar, PubMed/ Medline, the Google Search Engine, Science Direct, Research gate, and NCBI (National Center for Biotechnology Information) . Result: After reviewing many research papers, we can say that though use of pesticides increases agricultural production and control the vector borne diseases, but it has a severe effect on the bird’s metabolism, the nervous system, endocrine system, development, behavior, etc. Conclusion: When birds are exposed to pesticides for a long time it causes continuous health hazard for the population. To overcome this situation, intensive research should be carried out at molecular level, genetic level, etc. Rigid legal plans should set up against the extensive use of pesticides and concerned authorities shall look into its implement as well.